Suppression of the vortex induced vibration of slender cylindrical structures - Lamb, William Simon (Cranfield University, 1991)
This thesis presents the results of a detailed investigation into the performance of devices designed to suppress the vortex induced vibration of slender cylindrical structures. The phenomenon of vortex induced vibration is explained, followed by a literature review of published work on methods of suppression. The review revealed a lack of knowledge in several key areas relating to the performance of suppression devices. Furthermore, there were no analytical or empirical methods of predicting device performance. Slender cylindrical structures, such as marine risers, play a crucial role in the recovery of offshore oil reserves. An economic analysis was carried out which showed that vortex induced vibration can cause operational problems which significantly increase the risks and costs involved in offshore oil field exploitation. There was, therefore, an industrial need for more information on suppression devices and a means of predicting their performance. A large scale experimental investigation was performed to increase the understanding of suppression device performance under a variety of simulated offshore conditions, which included the effects of sheared flow, critical flow and partial suppression device coverage. Of the three traditional suppression devices tested, the fairing performed best, followed by the helical strake and then the perforated shroud. For the strake and shroud, the relationship between coverage and amplitude suppression was linear. For the fairing, however, the relationship became non-linear. With partial device coverage, the position of the device relative to the cylinder’s modal nodes and antinodes was very important. Sheared flow was found to increase the performance of all three suppression devices. In critical flow, vortex induced vibration of a bare cylinder was found to occur, but at reduced levels. Critical flow increased the performance of the suppression device. Computer based mathematical models have been developed which are capable of predicting the amplitude of vibration and drag force on bare cylinders, and cylinders fitted with suppression devices, under a variety of ambient conditions. The models were validated against the data obtained from the experimental programme. Two novel suppression devices have been invented, developed, tested and patented. They offer significant advantages over traditional devices for use in offshore operations.